Pengaruh Interaksi Sosial KAT Baduy Luar terhadap Persepsinya pada Kebutuhan Keluarga - Sihabudin, Ahmad (Mediator, 2008)
The objectives of this study are (1) to get description the family needs of the Outer Baduy Community, (2) to analyze factors that influence the perception of Outer Baduy Community towards the needs of their families; and (3) To get tentative model of Planned Changes, such as intervention, and things that need to be intervened to fulfill the needs of Outer Baduy Community’s Family. (5) Social Interaction through interpersonal communication and with the agent of change had significant relation to the perception of Heads of family on basic needs,safety, loved, and appreciated are felt, and the perception towards the satisfaction on safety, loved, and appreciated; To develop strategy and policy in fulfilling the needs of SCC family of Baduy can be created through the enhancement of standard family’s needs by making a centre of business practice, discussion forum (community information group), escalation of business facility, community participation, the support by opinion leader in Baduy community, private support, and the motive and the awareness to change is high.